Influence of nano zinc supplementation on digestibility and rumen fermentation parameters under in vitro conditions - Akash Mishra, Chander Datt, Kuldeep Dudi, Digvijay Singh, Goutam Kaul and Rajan Sharma (Indian Journal of Dairy Science, 2024)
In vitro experiments were conducted to find out the effects of supplementation of nano zinc (nZnO) @ 0, 1, 5, 10, 20 and 40 ppm to substrate on digestibility and rumen fermentation parameters. The substrate consisted of concentrate mixture and maize fodder in the ratio of 40:60. The results showed that supplementation of Zn in the form of ZnO nanoparticle at 10 and 20 ppm level increased gas production, digestibility, ME values, acetate production and cellulose digestion under in vitro conditions.